AUTOMATED NETWORK FAULT IDENTIFICATION SYSTEM (ANFIS) - Aliasaa, Nazrul Aman (Universiti Teknologi Petronas, 2006)
The aim of this project is to develop a system that identify faults in network environment automatically and suggest possible actions to be taken to attend the problem, besides managing the network device. Basically in a network environment, the faults occurred and being detected eventually by the users or the NA. However, there are existing systems which could be used to detect errors in LANenvironment. But mostly the scope of the existing system is far bigger and aimed to cater the need of network configuration in bigger organization. It is much more complex and complicated for smaller office which content a simple network configuration such as one-floor office workplace. For the project, the scope is within a simple network configuration with basic network appliances attached to the network environment. The project focuses more on single-floor office workplace area and simple network functions being done in the LANenvironment. Basically, the NMS developed will use one of network protocols named SNMP to monitor and gather information from network devices in monitoring and identifying error in the network. All errors being identified based on network appliances' behavior in the LAN environment. Once the errors have been detected, the NMS then will suggest possible solutions for the problems occurred and prompt it to the NA. The project's research is basically focusing more on analyzing the trap messages to identify the criticality of the network faults occurred in the network environment, besides also focusing on dividing network environment areas to analyze and categorized each fault that might possibly occur.